PROBLEMS IN TEACHING ENGLISH TO SCHOOL-AGE CHILDREN AND THEIR SOLUTIONS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article presents some ideas about the existing problems in teaching English to school-age children and their solutions. The article also presents some ideas about educational approaches, interactive methods, and game technologies that are considered effective in teaching English to school-age children.